Neoformation of clay in lateral root catchments of mallee eucalypts: a chemical perspective - Verboom, W.; Pate, J.; Aspandiar, Mehrooz (Oxford University Press, 2010)
Background and Aims: A previous paper (Annals of Botany 103: 673-685) described formation of clayey pavements in lateral root catchments of eucalypts colonizing a recently formed sand dune in south-west Western Australia. Here chemical and morphological aspects of their formation at the site are studied. Methods: Chemical and physical examinations of soil cores through pavements and sand under adjacent heath assessed build-up of salts, clay and pH changes in or below pavements. Relationships of root morphology to clay deposition were examined and deposits subjected to scanning electron microscopy and energy-dispersive X-ray analysis. Xylem transport of mineral elements in eucalypt and non-eucalypt species was studied by analysis of xylem (tracheal) sap from lateral roots. Key Results: The columns of which pavements are composed develop exclusively on lower-tier lateral roots. Such sites show intimate associations of fine roots, fungal filaments, microbiota and clay deposits rich in Si, Al and Fe. Time scales for construction of pavements by eucalypts were assessed. Cores through columns of pavemented profiles showed gross elevations of bulk density, Al, Fe and Si in columns and related increases in pH, Mg and Ca status in lower profiles. A cutting through the dune exhibited pronounced alkalinity (pH 7-10) under mallee woodland versus acidity (pH 5-6.5) under proteaceous heath. Xylem sap analyses showed unusually high concentrations of Al, Fe, Mg and Si in dry-season samples from column-bearing roots. Conclusions: Deposition of Al-Fe-Si-rich clay is pivotal to pavement construction by eucalypts and leads to profound chemical and physical changes in relevant soil profiles. Microbial associates of roots are likely to be involved in clay genesis, with parent eucalypts supplying the required key mineral elements and carbon sources. Acquisition of the Al and Fe incorporated into clay derives principally from hydraulic uplift from ground water via deeply penetrating tap roots.